PARTISIPASI MASYARAKAT DI DAERAH PEGUNUNGAN TERHADAP PERWUJUDAN GOOD GOVERNANCE - Muhammad Rais Rahmat Razak (AkMen JURNAL ILMIAH, 2018)
Community participation in mountainous areas towards the realization of Good Governance in Maiwa District, Enrekang Regency ". The study aims to 1) To determine the participation of the community in the mountainous area of ​​Maiwa Subdistrict 2) To find out the realization of good governance in Maiwa Subdistrict 3) To determine the effect of community participation in the mountainous region on the realization of good governance in Maiwa District, Enrekang Regency. The method used is descriptive quantitative research with frequency table analysis techniques to determine the condition of independent and dependent variables, namely the participation of people in mountainous regions as the variable "X" and the realization of good governance as a variable "Y", while to find out the formulation of associative problems using Simple Linear Regression Analysis . The results showed that the participation of the community in the mountainous area of ​​Maiwa Subdistrict was 69.2 in the "Good" category. The realization of 77.02 percent good governance in the category of "Good" while the influence of participation in the mountainous community towards the realization of good governance using simple linear regression analysis then processed using spss version 20.00 obtained R2 or R square values ​​from the summary table of 0.239 or 23.9 percent Community participation in mountainous regions has an influence on the realization of good governance in Maiwa Subdistrict, Enrekang Regency. While 76.1 percent is caused by other factors not examined.